2021
DOI: 10.1021/acs.est.0c06450
|View full text |Cite
|
Sign up to set email alerts
|

Ractopamine and Other Growth-Promoting Compounds in Beef Cattle Operations: Fate and Transport in Feedlot Pens and Adjacent Environments

Abstract: The current study represents a comprehensive investigation of the occurrence and fates of trenbolone acetate (TBA) and metabolites 17α-trenbolone (17α-TBOH), 17β-TBOH, and trendione (TBO); melengesterol acetate (MGA); and the less commonly studied β-andrenergic agonist ractopamine (RAC) in two 8 month cattle feeding trials and simulated rainfall runoff experiments. Cattle were administered TBA, MGA, or RAC, and their residues were measured in fresh feces, pen floor material, and simulated rainfall runoff from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In the US, RC has been detected in airborne particulate matter (4700 ng/g) in the feed yard and also in water bodies (271 ng/L) near the feed yard [81]. The transport of RC in water bodies and the feed yard is possible, as a recent study by Challis et al [82] in Canada confirmed that by feeding RC to feedlot cattle for 42 days, RC was still detected in the pen floor feces during (13 days; 3600 ng/g) and post feeding (37 days; 681 ng/g) such that run-off manure from pen floors and pasture contained RC at concentrations of 6300 and 2100 ng/L, respectively. The authors also showed that catch basins near commercial feedlots in Lethbridge, Canada, can contain RC at concentrations of 4000 to 27,000 ng/L in water and 234 to 1506 ng/g in sediment [82].…”
Section: Environmental Contaminationmentioning
confidence: 94%
See 3 more Smart Citations
“…In the US, RC has been detected in airborne particulate matter (4700 ng/g) in the feed yard and also in water bodies (271 ng/L) near the feed yard [81]. The transport of RC in water bodies and the feed yard is possible, as a recent study by Challis et al [82] in Canada confirmed that by feeding RC to feedlot cattle for 42 days, RC was still detected in the pen floor feces during (13 days; 3600 ng/g) and post feeding (37 days; 681 ng/g) such that run-off manure from pen floors and pasture contained RC at concentrations of 6300 and 2100 ng/L, respectively. The authors also showed that catch basins near commercial feedlots in Lethbridge, Canada, can contain RC at concentrations of 4000 to 27,000 ng/L in water and 234 to 1506 ng/g in sediment [82].…”
Section: Environmental Contaminationmentioning
confidence: 94%
“…The transport of RC in water bodies and the feed yard is possible, as a recent study by Challis et al [82] in Canada confirmed that by feeding RC to feedlot cattle for 42 days, RC was still detected in the pen floor feces during (13 days; 3600 ng/g) and post feeding (37 days; 681 ng/g) such that run-off manure from pen floors and pasture contained RC at concentrations of 6300 and 2100 ng/L, respectively. The authors also showed that catch basins near commercial feedlots in Lethbridge, Canada, can contain RC at concentrations of 4000 to 27,000 ng/L in water and 234 to 1506 ng/g in sediment [82]. Groundwater adjacent to cattle operations in Nebraska was also found to contain MON at concentrations ranging from 20 to 2080 ng/L, and the metabolites of steroidal hormones (i.e., estrone, testosterone, 4-androstenedione, and androsterone) ranging from 40 to 390 ng/L, and [83].…”
Section: Environmental Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The widespread use of pharmaceuticals for human and animal health management has increased substantially in recent decades (Challis et al., 2021; Kibuye et al., 2019). Carbamazepine (CBZ) is a typical antiepileptic drug widely used for the treatment of epilepsy, acute mania, and emotional disturbance.…”
Section: Introductionmentioning
confidence: 99%